Emergence of the G118R Pan-Integrase Resistance Mutation as a Result of Low Compliance to a Dolutegravir-Based cART - Helene Mens; Lasse Fjordside; Jannik Fonager; Jan Gerstoft (MDPI AG, 2022)
HIV-1 resistance towards integrase inhibitors is a potential threat of the success of HIV-1 combination treatment. G118R is a rare drug resistance mutation conferring pan-integrase resistance. Here, we describe the occurrence of G118R in a HIV-1 subtype-B-positive individual with major compliance problems, detected while the patient was on dolutegravir-based cART. We speculate the pre-selection of M184I/V aided the occurrence of G118R in this case, and discuss the robustness of dolutegravir-based therapies.